PENGARUH JENIS EDUKASI KESELAMATAN BERKENDARA TERHADAP PEMAHAMAN CALON PENGENDARA MOBIL DALAM MENGHADAPI KONFLIK LALU LINTAS - Chancard Basumerda; Rini Dharmastiti; Andi Rahadiyan Wijaya (Teknoin, 2014)
Data of traffic accidents in Indonesia reveal high rate of traffic incidence. Lack of discipline, low driving skill, poor knowledge of traffic rules of drivers are at high risk. Education on traffic rules can be obtained easily from both printed and electronic media. Large amount of information on safety driving, however, has not significantly reduced traffic accident rate. Some types of education on safety driving available at present may not be effective for would-be drivers. The objective of the study was to identify the effective education in safety driving on the knowledge of perspective drivers when encountering traffic conflict. The study was conducted on 30 respondents aged 15-17 yeras, who were classified into 3 groups: 10 respondents used visual texts, 10 respondents used visual pictures, and 10 respondents used Audio Visual (an instructor). All respondents took pre-test and post-test. The result showed the type of education influenced would-be drivers' comprehension. Visual pictures and audio visual (an instructor) were the most effective types of education on safety driving for perspective drivers.